以婕 發問時間: 科學數學 · 5 年前

(3x-3)^2*(2y+2)^2=(3x+2y-1)(3x-2y-5)那行為什麼?怎麼算的~?

Attachment image

2 個解答

評分
  • 5 年前
    最佳解答

    題目中的「*」應是「-」之誤。

    公式:a² - b² = (a + b)(a - b)

    設 a = 3x - 3 及 b = 2y + 2

    (3x - 3)² - (2y + 2)²

    = a² - b²

    = (a + b)(a - b)

    = [(3x - 3) + (2y + 2)] [(3x - 3) - (2y + 2)]

    = (3x - 3 + 2y + 2)(3x - 3 - 2y - 2)

    = (3x + 2y - 1)(3x - 2y - 5)

  • pui
    Lv 4
    5 年前

    (3x-3)^2 -(2y+2)^2

    =[(3x-3)-(2y+2)][(3x-3)+(2y+2)]

    =(3x-2y-5)(3x+2y-1)

還有問題?馬上發問,尋求解答。